Restoring the banana farming through macropropagation in South-Kivu, DR Congo - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
In the Democratic Republic of Congo, partners are working to restore banana farming in the South-Kivu region after a decade-long absence. Farmers are expressing their enthusiasm.